2013
DOI: 10.1161/circimaging.112.980052
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Aortic Valve Calcification Measured by Multidetector Computed Tomography in Aortic Stenosis

Abstract: A ortic stenosis (AS) is common in elderly people, affecting 2% of the population ≥65 years old and 4.6% of population ≥75 years old based on Doppler echocardiographic or community studies.1,2 Nowadays, the most common cause of AS is degenerative, and aortic valve calcification (AVC) is the intrinsic mechanism of valvular stiffening and obstruction. [3][4][5][6] Although degenerative AS has long been considered age related, recent studies have demonstrated that it is an active process involving biological path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
136
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 214 publications
(150 citation statements)
references
References 56 publications
13
136
1
Order By: Relevance
“…In addition, the focus of research on this topic has been to investigate sex differences in ventricular responses to pressure and volume overload posed by valvular disease rather than evaluating differences in the mechanism of AS itself 28. Nevertheless, 3 recent studies found important differences between men and women with regard to the development, extent, and progression of aortic valve calcifications supporting sex‐related differences in the mechanism of AS 29, 30, 31. Our findings of distinct risk profiles between men and women with AS at a community level support this notion and call for further research in sex‐specific disease mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the focus of research on this topic has been to investigate sex differences in ventricular responses to pressure and volume overload posed by valvular disease rather than evaluating differences in the mechanism of AS itself 28. Nevertheless, 3 recent studies found important differences between men and women with regard to the development, extent, and progression of aortic valve calcifications supporting sex‐related differences in the mechanism of AS 29, 30, 31. Our findings of distinct risk profiles between men and women with AS at a community level support this notion and call for further research in sex‐specific disease mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The summation of per‐slice lesion scores was performed individually for every aortic valve calcification score. In order to take into account the interpatient variability in valve size, we used the aortic valve calcification density, where aortic valve calcification was divided by the cross‐sectional aortic annulus area (π×[Aortic annulus diameter/2] 2 ) measured by echocardiography 14, 26, 27…”
Section: Methodsmentioning
confidence: 99%
“…16 Different cutoff values of aortic valve calcium score should be used in men (≥2000 AU or ≥480 AU/cm 2 ) versus women (≥1200 AU or ≥290 AU/ cm 2 ) to identify severe AS. 16,40 A potential explanation for this intriguing finding is that women have relatively more valvular fibrosis than men. Fibrosis may also contribute to valvular stenosis, but as opposed to calcification, it is not detected by MSCT.…”
Section: Cardiac Msctmentioning
confidence: 99%